EVALUASI KINERJA PELAYANAN AKADEMIK DI PERGURUAN TINGGI DENGAN BALANCED SCORECARD Studi Pada Pendidikan Tinggi Jarak Jauh Universitas Terbuka - FATMASARI, RHINI (Jurnal Ilmiah Educational Management, 2016)
This research’s aim is to evaluate the performance of academic services at high education of Open University (UT) by using balanced score card. Through evaluation, we will know how good the achievement of UT’s strategic plans that were run to achieve the vision and mission of UT. The perspectives of BSC evaluated at UT’s academic services are as follows (1) customer perspective, (2) financial perspective, (3) internal business perspective and, (4) innovation and learning perspective. The evaluation was done by interviewing, spreading the questioners of 358 respondents and document analysis of the report in 2013 and 2014 of UT’s Rector. The quantitative data processing was using Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The evaluation result showed that the performance of Academic Services of UT is in the very good condition (healthy condition), which has A category with 74,11 score of the whole performance. The evaluation result showed that the performance of academic services of UT in a customer perspective in a level of 67,54% of index, while 75,44% of index was on financial perspective, 78,32% of index was on internal business process perspective and 76,61% of index was on learning and growth perspective.